2020
DOI: 10.3390/app10062124
|View full text |Cite
|
Sign up to set email alerts
|

Deep Convolutional Neural Networks Based Analysis of Cephalometric Radiographs for Differential Diagnosis of Orthognathic Surgery Indications

Abstract: The aim of this study was to evaluate the deep convolutional neural networks (DCNNs) based on analysis of cephalometric radiographs for the differential diagnosis of the indications of orthognathic surgery. Among the DCNNs, Modified-Alexnet, MobileNet, and Resnet50 were used, and the accuracy of the models was evaluated by performing 4-fold cross validation. Additionally, gradient-weighted class activation mapping (Grad-CAM) was used to perform visualized interpretation to determine which region affected the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 30 publications
2
48
0
Order By: Relevance
“…Yang et al reported favorable result for automated detection of cyst and tumor of the jaw in panoramic images 13 . Lee et al reported that cephalometric images can be applied for differential diagnosis of orthognathic surgery and orthodontic treatment based on deep convolutional neural networks with 95.4 ~ 96.4% success rate 14 . More recently, there are many attempts for diagnosis of osteoarthritis of the temporomandibular joint based on cone-beam computed tomographic image using machine learning 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al reported favorable result for automated detection of cyst and tumor of the jaw in panoramic images 13 . Lee et al reported that cephalometric images can be applied for differential diagnosis of orthognathic surgery and orthodontic treatment based on deep convolutional neural networks with 95.4 ~ 96.4% success rate 14 . More recently, there are many attempts for diagnosis of osteoarthritis of the temporomandibular joint based on cone-beam computed tomographic image using machine learning 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, arti cial intelligence systems have been used to support decision making processes in the diagnosis and treatment planning of physicians. The neural network machine learning system was used in various treatment plans such as radiation therapy and orthognathic surgery and promising results were obtained [40][41][42]. As it is known, radiographic imaging plays an important role in the planning of dental implants.…”
Section: Discussionmentioning
confidence: 99%
“…examination in such gatherings and populace is yet to be researched. Irrelevant mistake in the estimations; exact, automated, basic, brisk, savvy, future orthodontic computerized apparatuses; and different types of cleft examples are the novelty of the current examination ( Lee et al, 2020 ; Kunz et al, 2020 ). The current investigation results may help the clinician in approaching where the impacts of essential CLP medical procedures are on various DC, supporting the restoration procedure in subjects with various sorts of NSCLP in building up a positive administration convention.…”
Section: Discussionmentioning
confidence: 99%
“…Oral clefts show an assortment of clinical inconsistencies ( Batwa et al, 2018 ). Lee et al (2020) and Kunz et al (2020) uncovered artificial intelligence (A.I.) into dentistry, particularly in orthodontics ready to break down obscure Late.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation